Propolis feeding modifies the expression of immune genes in challenged honey bees by injection with Paenibacillus larvae - Dominguez, Enzo (2023)
Bees do not seem to consume propolis under natural conditions, despite having a similar composition of polyphenols to that of pollen and nectar. These compounds have been shown to be active against bee pathogens such as the bacteria Paenibacillus larvae and the mite Varroa destructor, and to stimulate the expression of immune genes in worker bees when they are added to the nest. Overexpression of genes related to detoxification and reduction of fat bodies have also been observed in bees under forced ingestion. The gene expression of Toll18Wheeler, abaecin, hymenoptecin, vitellogenin (Vg), and domeless was determined using RT-qPCR, with the beta-actin gene as control, in bees fed for 10 days on a sugar and protein diet with (+P) and without (-P) propolis soft extract, and then subjected them to different immune treatments: Control (C), cutaneous injection (S), and injection of P. larvae (PL). The results showed that honey bees fed with propolis consumed significantly less food than control bees during the 10-day feeding (p=0.037). Besides, both feeding and treatments affected the relative expression of all studied genes, and there was an interaction between the main factors. Bees in the +P/PL and +P/S groups showed lower relative expression of abaecin and hymenoptecin than bees in the -P/PL (abaecin: p=3.36e-06; hymenoptecin: p=0.002) and -P/S (abaecin: p=1.78e-13; hymenoptecin: p=3.45e-13) groups, respectively. Moreover, feeding with propolis modified the expression of the Vg gene in response to bacterial injection. These results suggest that supplementation with propolis influences the regulation of immune system pathways in immune-challenged bees. This study contributes to answering the question of whether bees would benefit from consuming propolis under natural conditions.